Cover Picture: Lipid‐Bilayer‐Spanning DNA Nanopores with a Bifunctional Porphyrin Anchor (Angew. Chem. Int. Ed. 46/2013). Issue 46 (2nd October 2013) - Burns, Jonathan R.; Göpfrich, Kerstin; Wood, James W.; Thacker, Vivek V.; Stulz, Eugen; Keyser, Ulrich F.; Howorka, Stefan
<x xml:space="preserve">Abstract</x> Membrane nanopores self‐assembled from DNA are the most recent type of synthetic channels. Inserting negatively charged DNA origami structures into a hydrophobic membrane can be achieved with just two porphyrin‐based lipid anchors, as shown by S. Howorka and co‐workers in their Communication on page 12069 ff. Minimal chemical intervention paves the way to new DNA pores for label‐free biosensing and research into single molecules and biomimetic nanoarchitectures. (Simplified illustration of origami pores by Silvio Bianco, Hugh Martin, Jonathan R. Burns.)<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>